IMPROVING TEACHER SKILLS IN MAKING POWER POINT MEDIA THROUGH IN HOUSE TRAINING - Rostima, Siti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study is motivated by teachers’ skills in teaching, especially the lack of learning media used, which encouraged the researcher to conduct training through in-house training in order to improve teacher skills in making PowerPoint learning media. This study was an action research conducted at SDN 38 Mandau, with the subjects being 6 teachers. The technique of analyzing data used assessment guidelines. The results of the study showed that in Cycle I, the teachers' skill in making PowerPoints was 2.35, which was categorized as poor. After improvement, the teachers’ skills increased in Cycle II to 3.08, which was included in the good category. Based on the results of the study, it can be concluded that the teachers’ skills at SDN 38 Mandau have increased in making PowerPoint media through in-house training.